The effect of ERCC1 and ERCC2 gene polymorphysims on response to cisplatin based therapy in osteosarcoma patients - Hadeel Obiedat; Nasr Alrabadi; Eyad Sultan; Marwa Al Shatti; Malek Zihlif (BMC, 2018)
Abstract Background Cisplatin is one of the major drugs that used in the treatment of osteosarcoma. Cisplatin exerts its function by making cisplatin-DNA adducts culminating in cellular death. These adducts found to be repaired by nucleotide excision repair (NER) pathway. This study aimed to evaluate if polymorphisms in two main genes in the NER pathway, excision repair cross-complementing group 1 and 2 (ERCC1 and ERCC2) could affect the histological response to cisplatin based chemotherapy or clinical outcomes, particularly, event free survival (EFS) and overall survival (OS) rates. Method ERCC1 (C118T (rs11615) and C8092A (rs3212986)) and ERCC2 (A751C (rs171140) and G312A (rs1799793)) polymorphisms were analysed in 44 patients with osteosarcoma, who were treated with cisplatin based neoadjuvant chemotherapy. DNA was extracted from patient's formalin-fixed paraffin-embedded (FFPE) samples, patient's genotypes were determined by using polymerase chain reaction-restriction fragment length polymorphism PCR-RFLP assay. The distribution of the patients' genotype and the allele frequencies were reported. The association between each of these genotypes and many clinical and patho-histological parameters (e.g. EFS, OS and patho-histological response to treatment) was examined. The associations between gender, tumor location, presence of metastasis at diagnosis, histological subtypes, and type of neoadjuvant chemotherapy and between the histological response, EFS and OS rates were also examined. Results This study revealed that there was a positive and significant association between ERCC1 C8092 A genotypes and median EFS rate in years; patients who were carriers of C allele (CC & CA) were found to have longer EFS rates than patients with AA genotype (P value = 0.006) and the median EFS rates were respectively as following: 2.04, 0.24 years. As well, both the presence of metastasis and the histological subtype at the time of diagnosis, were able to affect the EFS rate but not the OS. However, there was a positive correlation between OS rate and the patients' primary response to treatment. Conclusions Our results suggested that ERCC1 8092 C allele may play a role as a candidate prognostic marker in patients with osteosarcoma.